Analysis of PPh 25 Payments and Its Implications for PPh 29: A Case Study of the ABC Foundation - Iftakhdianti, Nazwa Putri; Susanto, Febry Fabian (Universitas Mohammad Husni Thamrin, 2025)
This study aims to analyze the causes of the underpayment of Income Tax Article 29 at Yayasan ABC and to evaluate the effectiveness of Income Tax Article 25 payments as a monthly tax installment mechanism in reducing the year-end tax burden. This research is motivated by the discovery of a discrepancy in the 2022 Annual Corporate Income Tax Return, which occurred due to the absence of regular Article 25 installment payments throughout the fiscal year. The research employs a qualitative approach using a case study method. The data were obtained from tax documents such as the Annual Corporate Income Tax Return and interviews with the accounting staff who assisted the foundation’s tax reporting process. The findings indicate that Yayasan ABC reported Taxable Income (PKP) of Rp279,302,000 with a tax payable of Rp34,891,746. However, due to the absence of Article 25 installment payments during the year, this situation led to a discrepancy between the estimated installments and the actual tax payable. The impacts of not paying monthly installments include the potential imposition of interest penalties, the accumulation of financial burdens, and uncontrolled cash flow. Therefore, to address the underpayment issue, it is necessary to implement periodic Article 25 payments to avoid the accumulation of tax liabilities at the end of the year, strengthen tax planning to manage the strategy for Article 25 payments, and provide education from the accounting services office (KJA) to improve the foundation’s taxpayer understanding of taxation mechanisms.